PELAKSANAAN PEMBELAJARAN IPS DI SMP N 3 LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Wijayanti, Sri; Husnita, Liza; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
The problem of this research is how to get the permanent purposes of learning Social studies, collect the learning material, and collect the method and tools will be used and also assessment of learning Social studies. The purposes of this research isÂ to describes the goals of learning process, collect the learning material, method and tools will be used and also assessment learning of Social studies by teachers in SMP Negeri 3 Luhak Nan Duo West Pasaman Regency. This research is qualitative research that used natural setting as the proposes interpretation the phenomenon was happen and then doing by using all method. The location of this research is SMP Negeri 3 Luhak Nan Duo West Pasaman Regency with the informans is teacher and head master. This research collects data by using observation technique, interrogations, and documentation. Analysis data in this research is reduction data, presentation data, and conclusions. Implementation of Social studies in SMP Negeri 3 Luhak Nan Duo runs well. Teachers should have implementation of learning process and should used the material of learning that was available in the schools and methods that will be used by teacher must have variation based on the material in learning process, then the teachers should additions tools based on the ability. The assessments always carry out by teachers at the beginning to reminding material last weeks. In other hands some teachers not used the material based from lesson plan, thus some teachers only used one method. It is not suitable with the lesson plan that has been written. So that, teachers must doing learning process based on lesson plan that have been written.